A THEORETICAL BASED PHYSIOTHERAPY GOAL SETTING MODEL FOR ANTERIOR CRUCIATE LIGAMENT REHABILITATION. (18th November 2022) - Alexanders, Jenny; Perry, John; Douglas, Caroline
ABSTRACT: Background: Anterior Cruciate Ligament rehabilitation is a lengthy process and requires appropriate goal setting strategies to help optimize patient and athlete outcomes. From a global perspective, ACL injury incidences are continuing to rise, with Australia and the USA having one of the highest incidences of ACL injury rates in the athletic population. In addition, physiotherapists are expected by their professional regulatory body to effectively use goal setting practices. Design: Theoretical Goal Setting Model consisting of three phases: 1) Pre goal setting phase (empower); 2) goal implementation phase (strive); and 3) goal evaluation phase (attain). Discussion: This model provides physiotherapists with a useful process so that key aspects of setting goals are considered and incoporporated. This model showcases a necessary path a physiotherapist and patient must journey together in order to enhance rehabilitation outcomes. This model will also advance the  physiotherapists' awareness of the multi-stages of the patients goal desires, intentions and commitment to their rehabilitation. Conclusion: This model is a preliminary attempt to guide both practice, teaching, and research to ensure that goal setting practices in ACL rehabilitation are given an appropriate rehabilitative platform. The next stage is to empirically validate the practical application of the model and how each phase manifests.